Creating Shared Value and Competitive Advantage in Higher Education - Li, Songdi (2017)
Creating shared value (CSV) is considered as an evolution and development of traditional corporate social responsibility by some academics. CSV is specialized in its idea of combining social value and commercial value to create more value for all stakeholders. This dissertation analyse the potential of CSV theory application in higher education area through three CSV methods: reconceiving products and markets, redefining productivity in value chain and enabling the local cluster development. By conducting a qualitative research based on interview and case study, this dissertation finds out why the CSV concept can apply in the University of Nottingham, looks into the competitive advantages in CSV using, suggests two CSV application means in the University and try to generalise the findings to other Russell Group members.